The caregiver's companion : - Gonzalez-Mena, Janet (McGraw Hill, 2009)
Infants, Toddlers, and Caregivers is an ideal introduction to care and education in the first three years of life, featuring a respectful, cohesive approach inspired by Magda Gerber and Dr. Emmi Pikler, pioneers in what Gerber called “Educaring.” The text emphasizes the value of play and exploration, as well as giving careful attention to those caregiving times, when relationships grow and an abundance of learning occurs.